ANALISIS FAKTOR-FAKTOR PENYEBAB KERUSAKAN BAHAN PUSTAKA DI UPT PERPUSTAKAAN IAIN CURUP - Okky Rizkyantha; Dahlia Laini; Guntur Gunawan (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2022)
This study aims to find out what are the causes of damage to library materials at UPT IAIN Curup library and how to overcome the damage to library materials. This research is descriptive qualitative, which describes the facts and data collected and arranged in sentences. The data used are primary and secondary data. In addition, there are 3 data collection techniques in this study, namely: 1. observation, namely observing to collect data by looking directly at it, 2. Interviewing with specified informants 3. Documentation. Data analysis was carried out systematically, namely reducing data, presenting data and drawing conclusions. This study shows that the cause of damage to library materials at the UPT Library of IAIN Curup, the first from internal factors, namely the quality of the paper is not good. The second is from external factors, namely damage caused by insects, dust, air temperature and humidity, light, chemicals, humans. How to overcome damage to library materials at the UPT Library of IAIN Curup, One factor is caused by internal factors, taking backup books, discarding damaged pages and photocopies of the reservoir book and then repairing it and serving it again. the two external factors, namely: insects, the librarian simply gives camphor in between books and bookshelves. Dust, the librarian put a doormat at every entrance and dusted the bookshelves with sprays and covers. Temperature and humidity damage from temperature and humidity, librarians simply move bookshelves that are too close to the wall. Light, the librarian simply moves the book to a place that is not exposed to sunlight. chemistry by preparing a backup book. Human beings, librarians give sanctions to users who destroy books, reprimand, make banners about how to enter the library.